2021
DOI: 10.1101/2021.03.05.434135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 evolution in animals suggests mechanisms for rapid variant selection

Abstract: SARS-CoV-2 spillback from humans into domestic and wild animals has been well-documented. We compared variants of cell culture-expanded SARS-CoV-2 inoculum and virus recovered from four species following experimental exposure. Five nonsynonymous changes in nsp12, S, N and M genes were near fixation in the inoculum, but reverted to wild-type sequences in RNA recovered from dogs, cats and hamsters within 1-3 days post-exposure. Fourteen emergent variants were detected in viruses recovered from animals, including… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…This contrasts with what has been described in other animal species (e.g. tigers, lions, mink, cats, dogs, hamsters and ferrets) naturally and/or experimentally infected with the virus, in which characteristic mutations mainly in the S protein have been observed shortly after infection [22][23][24][25]. The findings in WTD can be partially explained by the high degree of homology of the human and deer ACE2 proteins species and in humans [19,[26][27][28][29].…”
Section: Discussioncontrasting
confidence: 65%
“…This contrasts with what has been described in other animal species (e.g. tigers, lions, mink, cats, dogs, hamsters and ferrets) naturally and/or experimentally infected with the virus, in which characteristic mutations mainly in the S protein have been observed shortly after infection [22][23][24][25]. The findings in WTD can be partially explained by the high degree of homology of the human and deer ACE2 proteins species and in humans [19,[26][27][28][29].…”
Section: Discussioncontrasting
confidence: 65%
“…For this, oropharyngeal and nasal swabs were collected from the animals up to 10 days after virus inoculation. Collected samples were sequenced and analyzed via a modern tiled amplicon technique [ 26 ] that allows for accurately determining single nucleotide and structural sequence variations in the viral populations. The results showed that viral sequences derived from cats, that were exposed via direct contact with other infected cats, had a high level of viral sequence similarity showing that novel viral mutations could be horizontally transmitted between cats [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collected samples were sequenced and analyzed via a modern tiled amplicon technique [ 26 ] that allows for accurately determining single nucleotide and structural sequence variations in the viral populations. The results showed that viral sequences derived from cats, that were exposed via direct contact with other infected cats, had a high level of viral sequence similarity showing that novel viral mutations could be horizontally transmitted between cats [ 26 ]. Cats also had fewer consensus viral sequences (i.e., less of the same virus sequences) and shared sequence variations as compared to those in the infected dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spillover of virus from humans or domestic animals into wildlife is concerning not only due to the possible deleterious effects on wildlife, but because these wild populations have the potential to act as reservoirs for SARS-CoV-2. Diseases that have an animal reservoir are inherently much more difficult to control and the spread of SARS-CoV-2 through animal populations could further contribute to the development of variants of concern (VoCs), potentially undermining the efficacy of medical countermeasures such as antivirals and vaccines (13, 14). Additionally, people who have close contact with wildlife, such as biologists, wildlife rehabilitators, and hunters and trappers, may be at higher risk of being exposed to the virus and of facilitating its spread among wildlife.…”
Section: Introductionmentioning
confidence: 99%